THE USE OF 'ONE STAYS REST STRAY' TECHNIQUE IN TEACHING READING COMPREHENSION OF NARRATIVE TEXT - Darma, Noviga (2013)
This study reports on the use of 'One Stays Rest Stray' (OSRS) technique in teaching reading comprehension of Narrative text. The aims of this study are to investigate the extent to which the use of OSRS technique helps students' reading comprehension and to examine students' responses to the use of OSRS technique in classroom. This study employed a qualitative research design, embracing characteristics of a case study. The data were obtained from non- participant classroom observation, written documents, and close and open- ended questionnaire. All the data were analyzed by using theories of aspects of reading comprehension (Morsy et al., 2010), supported the theories from Moreillon (2007), Westwood (2008), Burns et al. (2005), Klingner et al. (2007), Rice (2013), and Ueta (2005), theories of cooperative learning (Jacobs et al., 2006; Jolliffe, 2007; McDonell, 1992; Shoval & Shulruf, 2011), and theories of OSRS technique (Jacobs et al., 2006; Kagan, 2009; Surjosuseno, 2011; Agust et al., 2012; Felder & Brent, 2007). The results of the data in this study revealed that the use of OSRS technique helped students' reading comprehension by covering aspects of reading comprehension namely background knowledge, vocabulary knowledge, reading fluency, and comprehension strategies. The OSRS technique facilitated students in activating their background knowledge to connect to the text, finding out vocabulary knowledge in reading, improving students' reading fluency, and covering comprehension strategies so that they could engage in reading actively and comprehend the Narrative text better and easier. Besides, Students responded positively towards the use of OSRS technique in their learning. They felt motivated to participate and enjoyed in reading activities. Based on these findings, it is recommended that further research in the same field of this study investigate the use of the OSRS technique for teaching different types of texts and for different grade. Keywords: Reading Comprehension, Cooperative Learning, One Stays Rest Stray Technique, Narrative Text.